Learning by brewing tea: student experiences of a Kolb-aligned, constructivist, learning-oriented assessment in chemical engineering - Abidin, Zurina Zainal (Elsevier B.V., 2025)
This study evaluated a low-tech, low-cost tea-making task as a student-led experiential (SLE) assessment to introduce solid–liquid extraction in a second-year chemical engineering course. The design integrated Kolb's Experiential Learning Theory and constructivism within a learning-oriented assessment perspective. A mixed-methods approach combined a 10-item Likert questionnaire with open-ended reflections from the same cohort (N = 46). Quantitative analyses reported descriptive tendencies, Spearman inter-item associations (primary), and internal consistency while qualitative data underwent thematic analysis. Perceptions of the assessment were uniformly positive, and the scale showed excellent reliability (Cronbach's α = 0.952). Inter-item associations formed a coherent pattern consistent with a single experiential construct rather than isolated features. Qualitatively, 28 students’ comments converged on six themes which were knowledge and understanding (hands-on activity clarifies concepts), collaboration (peer dialogue and mutual correction), affective engagement (enjoyable, low-stakes), skill development (communication, confidence), autonomy and creativity (decision-making, problem solving), and learning-oriented element. Together, these findings indicated that concrete experience, structured peer interaction, and immediate feedback jointly support sense-making and participation. Overall, the tea-making SLE operated as assessment-as-learning, eliciting the very performances it sought to cultivate while maintaining a psychologically safe environment. Minor instrument refinements are recommended to enhance sensitivity at the top end and surface transfer more explicitly across future cohorts. The approach is inexpensive, scalable, and theoretically aligned, offering a practical template for embedding authentic, experiential and constructivist assessment in unit-operations teaching.